(untitled) (Foro de Educacion, 2024)
This paper presents two views of the contemporary political theory relating to the theme of justice and the State, Absolute Estatalismo Karl Schmitt and his theory Orthodox referring to the conflict. In Hannah Arendt came to be addressing the political consensus from the community and politics as public action. The political dilemma of justice in our times is ro- oted in the classical tradition policy ancient and modern but is exacerbated because of the rail- ways ideological conviction of the use of power, the handling of their political instrumentalization. The justice in the State has the features provided by the policy and level of social consensus or understanding that it troubled present.